PENGARUH MODEL THINK PAIR SHARE TERHADAP KEMAMPUANKOMUNIKASI MATEMATIS SISWA DI SDN 61 DAN MIN 3 PEKANBARU - Chindy Ariska; Zubaidah Amir MZ; Nurhasanah Bakhtiar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study about the effect of the Think Pair Share (TPS)cooperative learning model on students' mathematical communication skills. The study was a quasi-experimental method with a nonequivalent control group design. The study was conducted on class V of SDN 61 Pekanbaru and MIN 3 Pekanbaru in the academic year of 2021/2022. Class V which was studied at each school consisted of 32 students in the controlclass and 34 students in the experimental class at SDN 61 Pekanbaru. Class V at MIN 3 Pekanbaru consisted of 31 students in the control class and 34 students in the experimental class. The control class was treated without the TPS model and the experimental class was given the TPS model treatment by using the material of flat shapes. The results showed that the average of students from class V SDN 61 and MIN 3 increased after the implementation of the TPS learning model with average scores from 72.5 to 89.7 and 71.7 to 83.2 for each school. The results of the hypotheses significance from each school were 0.013 < 0.05 for class V atSDN 61 Pekanbaru and 0.006 < 0.05 for class V at MIN 3 Pekanbaru. It means that Ha was accepted, and Ho was rejected. Thus, it is proven that there was a significant effect of the TPS learning model on the students’ mathematical communication skills from class V SDN 61 Pekanbaru and MIN 3 Pekanbaru.